Elections 2008 au Ghana : esquisse de géographie électorale, entre permanences et recompositions - Isabelle Greig (EchoGéo)
The 2008 elections in Ghana reflect the democratic health of a country that has opted for an exemplary political change-over. Two trends shape the electoral geography that arises from the votes: the upholding of the ethno-regional bastions of the two dominant parties, and the swing of four regions to the opposition party, which shows complex developments on a local scale mainly due to socio-economic factors.